The Effectiveness of Progressive Muscle Relaxation Therapy on Preoperative Anxiety: A Systematic Review - Anisa Rohmah Tika; Susiana Candrawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Preoperative anxiety is a common condition experienced by patients awaiting surgery. One non-pharmacological method to reduce this anxiety is Progressive Muscle Relaxation (PMR) therapy, which helps lower anxiety by systematically tensing and relaxing muscle groups.Objective: To evaluate the effectiveness of PMR therapy in reducing anxiety levels in preoperative patients. Method: This study used a systematic literature review with the PRISMA approach. Data were collected from Google Scholar, EBSCO, and Semantic Scholar using the keywords